Properties of the excited electronic states of guanine quartet complexes with alkali metal cations - Milovanović Branislav Ž.; Petković Milena M.; Etinski Mihajlo R. (Journal of the Serbian Chemical Society, 2020)
G-quartets are supra-molecular structures that consist of four guanine molecules connected by eight hydrogen bonds. They are additionally stabilized by metal cations. In this contribution, the excited states of G-quartet and its complexes with lithium, sodium and potassium were studied by employing time-dependent density functional theory. The findings indicate that vertical excitations from the optimized ground state involve transitions from several bases, whereas excitations from the optimized lowest excited state include transitions from one base. The charge-transfer character of these states was analyzed. It was shown that the cations are able to modify positions of the maxima of the fluorescence spectra of the complexes. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 451-03-68/2020-14/200146]